Thermal desorption remediation effects on soil biogeochemical properties and plant performance: Global meta-analysis - Jiaxin Liao; Haowen Guo; Sanandam Bordoloi; Denian Li; Yuanxiang Zhang; Junjun Ni; Haoran Yuan; Xudong Zhao (Biogeotechnics, 2025)
Soil contamination remains a global problem, and numerous studies have been published for investigating soil remediation. Thermal desorption remediation (TDR) can significantly reduce the contaminants in the soil within a short time and consequently has been used worldwide. However, the soil properties respond to TDR differently and are dependent on the experimental set-up. The causative mechanisms of these differences are yet to be fully elucidated. A statistical meta-analysis was thus undertaken to evaluate the TDR treatment effects on soil properties and plant performance. This review pointed out that soil clay was reduced by 54.2%, while soil sand content was enhanced by 15.2% after TDR. This might be due to the release of cementing agents from clay minerals that resulted in the formation of soil aggregates. Soil electrical conductivity enhanced by 69.5% after TDR, which might be due to the heating-induced loss of structural hydroxyl groups and the consequent liberation of ions. The treatment of TDR leads to the reduction of plant germination rate, length, and biomass by 19.4%, 44.8%, and 20.2%, respectively, compared to that of control soil. This might be due to the residue of contaminants and the loss of soil fertility during the thermal process that inhibited plant germination and growth. Soil pH and sulfate content increased with heating temperature increased, while soil enzyme activities decreased with thermal temperature increased. Overall, the results suggested that TDR treatment has inhibited plant growth as well as ecological restoration.